Generation Charaterristics of Solid Waste and Plastic Waste: A Case Study in Long An Highschool - Nguyen Thi Tinh Au; Dang Viet Hung; Hoang Thi Tuyet Nhung (Journal of Technical Education Science, 2024)
Long An High School in Tan An, Long An, Vietnam, undertook a study to examine the generation and physical composition of solid and plastic waste. The study sampled 899 individuals, including officers, students, and teachers. Solid waste was classified into five primary categories and established three subcategories for plastic waste. The results showed that the average daily waste generation rate at Long An High School is 0.13 kg per student, including out-boarders who generate 0.028 kg per student, and boarding and part-boarding students who generate 0.18 kg/person/day. This rate is marginally lower than the waste generation rates observed in households. The analysis of plastic waste at the school indicated that it comprised 31% (35.65 kg/day) of the overall refuse generated. Boarding and part-boarding pupils generate a daily plastic waste generation rate of 0.055 kg, while out-boarders generate 0.01 kg per person. Long An Specialized High School receives recyclable plastic (46.5%), nylon bags (35.3%), and non-biodegradable polystyrene (foam delivery packaging) (18.2%) as its primary waste materials. Due to their lack of classification, these wastes are challenging to recycle. In terms of refuse generation per capita, male students produce 0.17 kg per male per day, while female students generate 0.15 kg per female per day, on average. Male students have an average discharge of 0.051 kg/male/day, which is 0.039 kg/female/day higher than female students' average discharges. In the case of plastic No. 6 (foam delivery boxes), male pupils emit three times more than female students.